2016
DOI: 10.1016/j.jsat.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Which Individual Therapist Behaviors Elicit Client Change Talk and Sustain Talk in Motivational Interviewing?

Abstract: Objective To identify individual therapist behaviors which elicit client change talk or sustain talk in motivational interviewing sessions. Method Motivational interviewing sessions from a single-session alcohol intervention delivered to college students were audio-taped, transcribed, and coded using The Motivational Interviewing Skill Code (MISC), a therapy process coding system. Participants included 92 college students and eight therapists who provided their treatment. The MISC was used to code 17 therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 11 publications
(17 reference statements)
12
58
0
3
Order By: Relevance
“…In other words, if momentum in the direction for or against change is the therapist's goal, these interventions may be optimal. This pattern of associations has been found in other sequential analyses, including with other heavy drinking clients recruited in the ED (Houck et al, 2010) and with heavy drinking, mandated, college students (Apodaca et al, 2016). Additionally, the use of simple reflections and paraphrasing may be critical to understanding and clarifying topics being presented by participants.…”
Section: Discussionsupporting
confidence: 74%
“…In other words, if momentum in the direction for or against change is the therapist's goal, these interventions may be optimal. This pattern of associations has been found in other sequential analyses, including with other heavy drinking clients recruited in the ED (Houck et al, 2010) and with heavy drinking, mandated, college students (Apodaca et al, 2016). Additionally, the use of simple reflections and paraphrasing may be critical to understanding and clarifying topics being presented by participants.…”
Section: Discussionsupporting
confidence: 74%
“…Further, under conditions of Skillful Connecting, Change Talk was more likely after Explore behaviors while Sustain Talk was less likely. This is consistent with recent sequential analysis work on MI, showing that affirmations in particular predicted Change Talk and suppressed Sustain Talk [65]. …”
Section: Discussionsupporting
confidence: 92%
“…Of the eight studies that examined both change and sustain talk, all studies found positive correlations between increased therapist empathy and MI spirit with client change and sustain talk except one small negative correlation between empathy and sustain talk (Apodaca et al, 2016). After a sensitivity analysis, no study, when removed, significantly altered the results.…”
Section: Discussionmentioning
confidence: 99%